Creencias irracionales en el desarrollo del individuo disminuidas mediante el modelo cognitivo conductual - Hurtado Torres, Cindy Irene (My University, 2019)
The present investigation describes the emotions as psychophysiological reactions that the person presents before relevant situations, the same ones can produce changes in the affective experience, the physiological activity or the expressive behavior of the people, it is also highlighted that there are two types of emotions: negative and positive according to their intensity, duration, frequency, expression and for their contribution to the well-being or significant discomfort of the person; In relation to this and starting from the negative emotions, the fear stands out as one of the most important in this classification. On the other hand, a description of irrational beliefs is presented, which are defined as those misguided and illogical ideas that affect the psychosocial functions of the person, causing a disturbance in the ability to think coherently, which in turn leads to alterations in behavior and emotions, affecting their psychological well-being, their abilities and personal growth. In the background and not least, a therapeutic plan, steps and tools necessary to work in the reduction of irrational beliefs that interfere in the normal development of people are presented. Within the intervention process, the cognitive behavioral approach is used to count on a large number of instruments and their effectiveness in the treatment to modify the behaviors and thoughts that manage the psychological problem, in order to nurture the patient's abilities so that he can overcome the psychological difficulties that arise in his daily life and may have a better life quality.
La presente investigación describe las emociones como reacciones psicofisiológicas que presenta la persona ante situaciones relevantes, las mismas que pueden producir cambios en la experiencia afectiva, la actividad fisiológica o conducta expresiva de las personas, se destaca además, existen dos tipos de emociones: negativas y positivas de acuerdo a su intensidad, duración, frecuencia, expresión y por su contribución al bienestar o malestar significativo de la persona; en relación a ello y partiendo de las emociones negativas se destaca el miedo por ser una de las más importantes en esta clasificación. Por otra parte se presenta una descripción sobre las creencias irracionales las cuales se definen como aquellas ideas desacertadas e ilógicas que afectan las funciones psicosociales de las persona ocasionando perturbación en la capacidad para pensar de forma coherente lo que desencadena a su vez en alteraciones en el comportamiento y las emociones, afectando su bienestar psicológico, sus capacidades y el crecimiento personal.
Keywords: EMOCION; CREENCIA IRRACIONAL; CONDUCTUA; COGNITIVO